The economic cost of cancer treatment in Iran - Alireza Jabbari; Marziye Hadian; Elaheh Mazaheri; Zahra Khakdel Jelodar (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: With more than 12 million new cases of cancers and nearly 7.6 million deaths worldwide in 2020, cancer is currently the third leading cause of mortality in the world. The costs spent on treating patients with cancer account for a significant amount of healthcare costs. Healthcare expenditures for cancer treatment have also increased significantly and are projected to skyrocket further over the next decade. This study was conducted to determine medical and non-medical direct costs for the prevention of cancer in patients hospitalized in 10 selected educational hospitals in Iran. MATERIALS AND METHODS: The study employed a cross-sectional design and was conducted in 10 selected educational hospitals in Tabriz, Tehran, Isfahan, Mashhad, and Shiraz in 2020. Using a researcher-made questionnaire, we assessed direct medical costs and direct non-medical costs of cancer in patients over 20 years old with kinds of breast, prostate, leukemia, lymphatic, stomach, liver, lung, bladder, uterine, and intestine cancers who undertook oncology treatments (n = 2410). Data were analyzed using descriptive statistics including mean and standard deviation and analytic statistics such as Kolmogorov-Smirnov, analysis of variance, and t-test, using SPSS 18 and P ≤0.05. RESULT: The mean direct non-medical cost paid out of pocket per month was $99.6 ± $10.81 USD, and the mean direct medical cost per month was $1029.4 ± $68.5 USD. The total cost paid by the patients was $889.4 ± 69.81 USD per month. CONCLUSION: Given the increasing number of patients with cancer, it is necessary to increase the number of special centers for the prevention and treatment of cancers. Dissemination of information about the costs of illnesses and their complications enables decision-makers to make a proper comparison between different uses of resources. Moreover, to support the patients, the health system must implement plans to decrease out-of-pocket payments by patients.